America's working women: A documentary history, 1600 to the present - Baxandall, Rosalyn Fraad, (1939- ...).; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

La formation professionnelle des femmes : gage pour l'avenir ou voie d'évitement? - Desmarais, Danielle; Provost, Monique; Legault, Sylvie (Service aux collectivités de l'UQAM/Conseil d'intervention pour l'accès des femmes au travail, 1995)
Ce rapport présente les résultats d'une recherche sur la formation professionnelle des femmes. Il expose le profil des répondantes, le parcours des femmes en formation professionnelle, leur cheminement en formation générale au secondaire, en formation professionnelle (secondaire ou collégiale), en stage, leur cheminement en emploi ainsi que leurs conditions de vie actuelles (emplois obtenus, types de salaires, etc.).
Keywords: 1900-1999; 1990-1999; SAC; amériques; femmes*; formation professionnelle; périodes historiques; québec; rapport; recherche partenariale; régions géographiques; thématiques; travail

Regard sur la culture organisationnelle communautaire : deux études de cas - Fournier, Danielle; Guberman, Nancy; Beeman, Jennifer; Gervais, Lise (Services aux collectivités de l'UQAM, 1995)
Ce rapport présente les résultats d'une recherche concernant la culture organisationnelle d'une maison des jeunes et d'un centre de femmes : lieux, membres, objectifs, activités, équipe de travail, conseil d'administration, financement, mode de gestion et structure, intégration des membres aux instances formelles, relations permanent-e-s et membres, travail salarié, professionnalisation, conditions de travail, rapport ... la vie privée et ... l'État.
Keywords: SAC; discipline; entrepreneuriat; groupes de femmes; maisons de jeunes; organisation et ressources humaines; sciences de la gestion; thématiques; travail